Anaerobic curable adhesive composition, cured product thereof, and laminate

The anaerobic curable adhesive composition, comprising alicyclic (meth)acrylate, phosphoric acid (meth)acrylate, and a silane coupling agent, addresses the issue of insufficient peel strength under high-temperature water conditions, achieving a significant improvement in adhesive performance.

JP2025069879APending Publication Date: 2025-05-01TOAGOSEI CO LTD

Patent Information

Application Number
JP2023179879
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-05-01

AI Technical Summary

Technical Problem

Existing anaerobic curable adhesive compositions do not exhibit sufficient peel strength under high-temperature water conditions, which is a critical requirement for various industrial applications.

Method used

An anaerobic curable adhesive composition comprising alicyclic (meth)acrylate, phosphoric acid (meth)acrylate (excluding those with halogen atoms in the side chains), and a silane coupling agent, with a total content of these components ranging from 1% to 10% by mass, and a silane coupling agent content less than 5% by mass, is used to achieve enhanced peel strength.

Benefits of technology

The proposed adhesive composition demonstrates excellent peel strength under high-temperature water conditions, with an average peel strength of 0.3 N/mm or more at 95°C, thereby meeting the requirements for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025069879000002
    Figure 2025069879000002
  • Figure 2025069879000001
    Figure 2025069879000001
Patent Text Reader

Abstract

To provide an anaerobic curable adhesive composition having excellent peel strength under high-temperature water conditions.SOLUTION: An anaerobic curable adhesive composition comprises at least an alicyclic (meth)acrylate and a phosphoric (meth)acrylate, with the exception of those having a halogen atom in the side chain, wherein the total content of the phosphoric (meth)acrylate and a silane coupling agent is 1 mass% or more and 10 mass% or less relative to the total amount of the anaerobic curable adhesive composition, and the content of the silane coupling agent is less than 5 mass% relative to the total amount of the anaerobic curable adhesive composition.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an anaerobic curing adhesive composition, a cured product, and a laminate. [Background technology]

[0002] In order to reduce the weight of automobiles, electronic devices, and other components, adhesive fastening methods are becoming mainstream, replacing the conventional bolt fastening methods.

[0003] Examples of adhesives that are used include UV-curable adhesives, thermosetting adhesives, anaerobic curing adhesives, and moisture-curable adhesives. Among them, anaerobic curing adhesives are different from UV-curable adhesives and thermosetting adhesives in that they do not require a UV irradiation device or a heating device when curing the adhesive. Furthermore, while UV-curable adhesives and thermosetting adhesives are limited in the substrates that they can be bonded to, anaerobic curing adhesives can be used on a variety of substrates. Furthermore, anaerobic curing adhesives have higher heat resistance than moisture curing adhesives (eg, instant adhesives), and therefore can be used over a wider temperature range.

[0004] As a conventional anaerobic curing adhesive, Patent Document 1 discloses an anaerobic curing adhesive characterized by containing the following components (A) to (E): Component (A): Compound having a radically polymerizable functional group Component (B): Radical initiator (C) Component: a compound selected from the group consisting of saccharin, N,N-diethyl-p-toluidine, N,N-dimethyl-o-toluidine, tolidine, and maleic acid Component (D): Benzotriazole compound or hydrazine compound Component (E): A polythiol compound having two or more thiol groups

[0005] Patent Document 2 discloses a radical-polymerizable adhesive composition for adhesively bonding laminated steel plates, which has a value of 8.0 MPa or more as determined in the tensile shear adhesive strength test for electrical steel plate described below, and which contains component (A): a radical-polymerizable compound, component (B): a radical polymerization initiator, and component (C): a phosphate ester compound having a group represented by the following general formula (1) or (2): Tensile shear adhesive strength to electrical steel sheet: A 0.1 g primer composition containing 100 parts by mass of punching oil, 100 parts by mass of ethanol, and 0.5 parts by mass of copper 2-ethylhexanoate was applied to a test piece of electrical steel sheet measuring 25 mm in width, 100 mm in length, and 0.3 mm in thickness, and the test piece was left to dry at 25°C for 3 hours. Next, 0.1 g of a radically polymerizable adhesive composition for adhesive laminated steel sheets is applied to the primer-treated test piece, and the other primer-treated test piece is placed on top of it so that the long end of the test piece is 10 mm long. A 100 g weight is placed on the bonded surface and the test piece is fixed at 25°C for 24 hours to obtain an adhesive test piece. Next, the ends of the adhesive test piece are pulled with a universal tensile tester at a pulling speed of 50 mm / min, and the tensile shear adhesive strength (MPa) is measured in accordance with JIS K6850 (1999). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2016-117851 A [Patent Document 2] International Publication No. 2019 / 123885

[0007] Patent Document 1 examines the interlocking strength (shear strength) of an anaerobic curing adhesive, but does not examine the peel strength under high-temperature water conditions.

[0008] Patent Document 2 examines the tensile shear strength of the radically polymerizable adhesive composition for adhesively bonding laminated steel sheets, but does not examine the peel strength under high-temperature water conditions. Summary of the Invention [Problem to be solved by the invention]

[0009] An object of one embodiment of the present disclosure is to provide an anaerobic curing adhesive composition that has excellent peel strength under high-temperature water conditions. Another problem to be solved by another embodiment of the present disclosure is to provide a cured product of the above-mentioned anaerobic curing adhesive composition, and a laminate having the above-mentioned cured product. [Means for solving the problem]

[0010] Specific means for solving the above problems include the following aspects. <1> An anaerobic curing adhesive composition comprising at least an alicyclic (meth)acrylate and a (meth)acrylate phosphate (excluding those containing a halogen atom in the side chain), wherein the content of the (meth)acrylate phosphate and the silane coupling agent is from 1 mass % to 10 mass % based on the total amount of the anaerobic curing adhesive composition, and the content of the silane coupling agent is less than 5 mass % based on the total amount of the anaerobic curing adhesive composition. <2> containing difunctional ethylenically unsaturated compounds, <1> The anaerobic curing adhesive composition according to claim 1 . <3> The content of the alicyclic (meth)acrylate is 30% by mass or more and 70% by mass or less based on the total amount of the anaerobic curing adhesive composition; <1> or <2> The anaerobic curing adhesive composition according to claim 1 . <4> The content of the bifunctional ethylenically unsaturated compound is 20% by mass or more and 60% by mass or less based on the total amount of the anaerobic curing adhesive composition. <2> The anaerobic curing adhesive composition according to claim 1 . <5> The bifunctional ethylenically unsaturated compound is a polymer or oligomer having two or more (meth)acryloyl groups in one molecule. <2> or <4> The anaerobic curing adhesive composition according to claim 1 . <6> The polymer or oligomer having two or more (meth)acryloyl groups in one molecule has a weight average molecular weight of 15,000 or less and a glass transition temperature of 0°C or less. <5> The anaerobic curing adhesive composition according to claim 1 . <7> The silane coupling agent has a thiol group. <1> ~ <6> 13. The anaerobic curing adhesive composition according to claim 12. <8> The viscosity at 25°C is 50 mPa·s to 1,000 mPa·s. <1> ~ <7> 13. The anaerobic curing adhesive composition according to claim 12. <9> <1> ~ <8> 2. A cured product obtained by curing the anaerobic curing adhesive composition according to claim 1. <10> The adhesive layer includes a first substrate, an adhesive layer, and a second substrate in this order, <9> A laminate comprising the cured product according to claim 1. <11> The average peel strength under high-temperature water conditions of 95°C when peeling the adhesive layer from the first substrate or the second substrate is 0.3 N / mm or more. <10> The laminate according to claim 1. Effect of the Invention

[0011] An object of one embodiment of the present disclosure is to provide an anaerobic curing adhesive composition that has excellent peel strength under high-temperature water conditions. The present disclosure also makes it possible to provide a cured product of the anaerobically curable adhesive composition, and a laminate having the cured product. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a schematic diagram for explaining a method for measuring the average peel strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] In the present disclosure, a numerical range expressed using "~" means a range including the numerical values ​​described before and after "~" as the lower and upper limits. In the numerical ranges described in stages in the present disclosure, the upper or lower limit described in a certain numerical range may be replaced with the upper or lower limit of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit described in a certain numerical range may be replaced with a value shown in the examples. In the present disclosure, "(meth)acrylic" refers to both or either of acrylic and methacrylic, and "(meth)acrylate" refers to both or either of acrylate and methacrylate. In the present disclosure, "mass %" and "weight %" are synonymous, and "parts by mass" and "parts by weight" are synonymous. Also, in the present disclosure, combinations of two or more preferred aspects are more preferred aspects.

[0014] The contents of the present disclosure will be described in detail below.

[0015] [Anaerobic curing adhesive composition] The anaerobic curing adhesive composition according to the present disclosure contains at least an alicyclic (meth)acrylate and a (meth)acrylate phosphate (excluding those containing halogen atoms in the side chain), and may contain other components as necessary. In the anaerobic curing adhesive composition according to the present disclosure, the total content of the (meth)acrylate phosphate and the silane coupling agent is 1% by mass or more and 10% by mass or less based on the total amount of the anaerobic curing adhesive composition, and the content of the silane coupling agent is less than 5% by mass based on the total amount of the anaerobic curing adhesive composition.

[0016] The mechanism by which the anaerobically curable adhesive composition according to the present disclosure exhibits excellent peel strength under high-temperature water conditions is presumed to be as follows. The alicyclic (meth)acrylate contained in the anaerobic curing adhesive composition has an alicyclic structure, and therefore the hydrophobicity of the anaerobic curing adhesive composition is improved compared to (meth)acrylates that do not have an alicyclic structure. In addition, by containing a predetermined amount of phosphate (meth)acrylate (excluding those containing halogen atoms in the side chain) in the anaerobic curing adhesive composition, the phosphate group of the phosphate (meth)acrylate reacts at the interface with the substrate (particularly a metal substrate), and the adhesion is improved due to strong ionic bonds. Furthermore, by setting the content of the silane coupling agent in the anaerobic curing adhesive composition within a predetermined range, the silane coupling agent crosslinks the organic matter contained in the anaerobic curing adhesive composition and the substrate (particularly the metal substrate) at the interface, thereby further improving the adhesion. From the above, it is presumed that the anaerobic curing adhesive composition according to the present disclosure has excellent peel strength in high-temperature water.

[0017] <Alicyclic (meth)acrylate> The anaerobic curing adhesive composition according to the present disclosure contains an alicyclic (meth)acrylate, which can suppress cure shrinkage and improve adhesion to a substrate.

[0018] The alicyclic (meth)acrylate is not particularly limited, and may be a monocyclic (meth)acrylate, a bicyclic (meth)acrylate, or a tricyclic or higher polycyclic (meth)acrylate.

[0019] Monocyclic (meth)acrylates include, for example, cyclopropyl (meth)acrylate, cyclobutyl (meth)acrylate, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cyclooctyl (meth)acrylate, cyclononyl (meth)acrylate, and cyclodecyl (meth)acrylate.

[0020] Bicyclic (meth)acrylates include, for example, isobornyl (meth)acrylate and norbornyl (meth)acrylate.

[0021] Polycyclic (meth)acrylates include, for example, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyalkyl (meth)acrylate, and adamantyl (meth)acrylate.

[0022] Among the above alicyclic (meth)acrylates, monocyclic (meth)acrylates and bicyclic (meth)acrylates are preferred from the viewpoint of the glass transition temperature (Tg) of the cured product after curing. Among the monocyclic (meth)acrylates, 1,4-cyclohexanedimethanol monoacrylate, 3,3,5-trimethylcyclohexyl (meth)acrylate, or cyclohexyl (meth)acrylate are preferred, and cyclohexyl (meth)acrylate is more preferred. Among the bicyclic (meth)acrylates, dicyclopentadiene (meth)acrylate and 3,4-epoxycyclohexylmethyl (meth)acrylate are more preferred. Among these, 3,4-epoxycyclohexylmethyl (meth)acrylate is particularly preferred.

[0023] The alicyclic (meth)acrylate may be contained alone or in combination of two or more kinds. The content of the alicyclic (meth)acrylate is preferably 30 mass % to 70 mass %, more preferably 35 mass % to 65 mass %, and further preferably 40 mass % to 60 mass %, based on the total amount of the anaerobic curing adhesive composition.

[0024] <(Meth)acrylate Phosphate> The anaerobic curing adhesive composition according to the present disclosure contains a (meth)acrylate phosphate (excluding those containing a halogen atom in the side chain). By containing a (meth)acrylate phosphate (excluding those containing a halogen atom in the side chain), the adhesion between the anaerobic curing adhesive composition and a substrate (particularly a metal substrate) is improved.

[0025] There are no particular limitations on the phosphate (meth)acrylate as long as it does not contain a halogen atom in the side chain, and monoesters, diesters, and triesters can be used. The (meth)acrylate phosphate preferably has a structure in which a (meth)acryloyloxy group and a phosphate group are linked by a linker. Examples of the linker include a hydrocarbon group having 2 to 20 carbon atoms. The hydrocarbon group may have -O- inserted therein like polyether, may have hydrogen substituted with a substituent other than a halogen atom (-OH, -COOH, etc.), or may be unsubstituted.

[0026] Examples of the (meth)acrylate phosphate that does not contain a halogen atom in the side chain include 2-(meth)acryloyloxyethyl acid phosphate, di-(2-methacryloyloxyethyl) phosphate, 2-(meth)acryloyloxypropyl acid phosphate, 2-(meth)acryloyloxybutyl acid phosphate, acid phosphooxy polyoxypropylene glycol monomethacrylate, and acid phosphooxy polyoxyethylene glycol monomethacrylate. Of these, 2-(meth)acryloyloxyethyl acid phosphate and di-(2-methacryloyloxyethyl) phosphate are preferred, and 2-(meth)acryloyloxyethyl acid phosphate is more preferred.

[0027] Examples of commercially available products include 2-methacryloyloxyethyl acid phosphate (Unichemical Co., Ltd., Phosmer M), acid phosphooxy polyoxyethylene glycol monomethacrylate (Unichemical Co., Ltd., Phosmer PE), acid phosphooxy polyoxypropylene glycol monomethacrylate (Unichemical Co., Ltd., Phosmer PP), 2-acryloyloxyethyl acid phosphate (Kyoeisha Chemical Co., Ltd., Light Acrylate P-1A(N)), 2-methacryloyloxyethyl acid phosphate (Kyoeisha Chemical Co., Ltd., Light Ester P-1M), and di-(2-methacryloyloxyethyl) phosphate (Kyoeisha Chemical Co., Ltd., Light Ester P-2M).

[0028] The (meth)acrylate phosphate not containing a halogen atom in the side chain may contain one type alone or two or more types. The content of the phosphate (meth)acrylate having no halogen atom in the side chain is preferably 1% by mass or more and 10% by mass or less based on the total amount of the anaerobic curing adhesive composition. The anaerobic curing adhesive composition of the present disclosure may contain "phosphate (meth)acrylate having a halogen atom in the side chain" as an impurity, within a range that does not significantly impair the effects of the present invention. The content of "phosphate (meth)acrylate having a halogen atom in the side chain" as an impurity is preferably 0.01% by mass or less based on the total amount of the anaerobic curing adhesive composition.

[0029] In the anaerobic curing adhesive composition of the present disclosure, the total content of the (meth)acrylate phosphate and the silane coupling agent described below is 1% by mass or more and 10% by mass or less with respect to the total amount of the anaerobic curing adhesive composition. If the total content is less than 1% by mass, the bonding with the interface is insufficient, resulting in insufficient peel strength under high-temperature water conditions. If the total content exceeds 10% by mass, the two tend to bond to each other, leading to an increase in elastic modulus and a tendency to become hard, resulting in insufficient peel strength under high-temperature water conditions. Among these, the total content of the (meth)acrylate phosphate and the silane coupling agent described below is more preferably 2% by mass or more and 6% by mass or less, and particularly preferably 2% by mass or more and 4% by mass or less, from the same viewpoint as above.

[0030] When the anaerobic curing adhesive composition does not contain a silane coupling agent described below, the content of the (meth)acrylate phosphate not containing a halogen atom in the side chain is preferably from 1 to 10 mass%, more preferably from 1 to 8 mass%, and even more preferably from 1 to 4 mass%, based on the total amount of the anaerobic curing adhesive composition.

[0031] When the anaerobic curing adhesive composition contains a silane coupling agent described later, the content of the (meth)acrylate phosphate having no halogen atom in the side chain is preferably 9% by mass or less, more preferably 7% by mass or less, even more preferably 5% by mass or less, and particularly preferably 3% by mass or less, based on the total amount of the anaerobic curing adhesive composition. The lower limit is, for example, 0.5% by mass or more.

[0032] <Silane coupling agent> The anaerobically curable adhesive composition according to the present disclosure preferably contains a silane coupling agent. By containing a silane coupling agent, the interfacial adhesive strength between a cured product of the anaerobically curable adhesive composition and a substrate can be further increased.

[0033] The silane coupling agent preferably has a reactive functional group in addition to the alkoxysilyl group, and examples of the silane coupling agent include coupling agents having an amino group, an epoxy group, a (meth)acryloyl group, a vinyl group, and a thiol group as the reactive functional group. Among these, from the viewpoint of peel strength, silane coupling agents having an epoxy group, a (meth)acryloyl group or a thiol group as a reactive functional group are preferred, and silane coupling agents having a thiol group are more preferred.

[0034] Examples of silane coupling agents having an epoxy group as a reactive functional group include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltriethoxysilane, 8-glycidoxyoctyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 5,6-epoxyhexyltrimethoxysilane, 5,6-epoxyhexylmethyldimethoxysilane, 5,6-epoxyhexylmethyldiethoxysilane, and 5,6-epoxyhexyltriethoxysilane.

[0035] Examples of silane coupling agents having a (meth)acryloyl group as a reactive functional group include 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, and 8-(meth)acryloxyoctyltrimethoxysilane.

[0036] Examples of silane coupling agents having a thiol group as a reactive functional group include 3-mercaptopropyltrimethoxysilane and 3-mercaptopropyltriethoxysilane.

[0037] The anaerobic curing adhesive composition according to the present disclosure may contain one type of silane coupling agent alone, or may contain two or more types of silane coupling agents. The content of the silane coupling agent is less than 5% by mass, and may be 0% by mass, based on the total amount of the anaerobic curing adhesive composition. The content of the silane coupling agent is preferably 4% by mass or less, more preferably 3% by mass or less, based on the total amount of the anaerobic curing adhesive composition. The lower limit is preferably 1% by mass or more.

[0038] <Difunctional ethylenically unsaturated compounds> The anaerobic curing adhesive composition of the present disclosure preferably contains a difunctional ethylenically unsaturated compound. The difunctional ethylenically unsaturated compound may be any one of a monomer, an oligomer, and a polymer, and is preferably a polymer and / or an oligomer. A preferred difunctional ethylenically unsaturated compound is a polymer and / or an oligomer having two or more (meth)acryloyl groups in one molecule.

[0039] In the present disclosure, an oligomer refers to a polymer having a weight-average molecular weight of 500 or more and less than 5,000. Also, a polymer refers to a polymer having a weight-average molecular weight of 5,000 or more.

[0040] In the present disclosure, the weight average molecular weight means a value obtained by converting the weight average molecular weight measured by GPC (gel permeation chromatography) using polystyrene as a standard substance. The weight average molecular weight can be determined, for example, by the following procedure. Separation is performed using a gel permeation chromatograph (HLC-8320GPC manufactured by Tosoh Corporation) in tetrahydrofuran solvent at 40°C using a GPC column "TSK gel SuperMultiporeHZ-M" (manufactured by Tosoh Corporation), and the weight average molecular weight converted into standard polystyrene is calculated from the retention time.

[0041] The (meth)acryloyl group contained in the polymer or oligomer having two or more (meth)acryloyl groups in one molecule is preferably at a terminal position, but may be contained in a monomer unit constituting the main chain of the polymer or oligomer.

[0042] The polymer and / or oligomer having two or more (meth)acryloyl groups in one molecule is not particularly limited, but from the viewpoint of adhesive strength at high temperatures, it is preferably at least one selected from the group of polymers or oligomers consisting of urethane (meth)acrylate, epoxy (meth)acrylate, ester (meth)acrylate, isoprene-based (meth)acrylate, or hydrogenated isoprene-based (meth)acrylate, more preferably urethane (meth)acrylate or epoxy (meth)acrylate, and even more preferably urethane (meth)acrylate. Moreover, the polymer and / or oligomer having two or more (meth)acryloyl groups in one molecule is preferably a polymer or oligomer having a (meth)acryloyl group at its terminal, from the viewpoint of adhesive strength at high temperatures.

[0043] Examples of the urethane (meth)acrylate include a reaction product of a polyhydric alcohol, a polyisocyanate and a hydroxy(meth)acrylate compound, and a reaction product of a polyisocyanate and a hydroxy(meth)acrylate compound without using a polyhydric alcohol. Specific examples of polyhydric alcohols include polyether polyols such as polypropylene glycol and polytetramethylene glycol, polyester polyols obtained by reacting a polyhydric alcohol with a polybasic acid, caprolactone polyols obtained by reacting a polyhydric alcohol with a polybasic acid and ε-caprolactone, and polycarbonate polyols (e.g., polycarbonate polyols obtained by reacting 1,6-hexanediol with diphenyl carbonate), and the like. Specific examples of polyisocyanates include alicyclic polyisocyanates (isophorone diisocyanate, dicyclopentanyl diisocyanate, etc.), aliphatic polyisocyanates (hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, etc.), and aromatic polyisocyanates (tolylene diisocyanate, xylylene diisocyanate, diphenylmethane-4,4'-diisocyanate, etc.). As the urethane (meth)acrylate, those produced from a polyether polyol, a polyester polyol or a polycarbonate polyol as a raw material polyol are preferred in terms of excellent adhesive strength, and as the raw material organic polyisocyanate, those produced from isophorone diisocyanate, hexamethylene diisocyanate or xylene diisocyanate are preferred in terms of excellent adhesive strength.

[0044] Examples of the urethane (meth)acrylate include urethane (meth)acrylate having a polybutadiene skeleton, urethane (meth)acrylate having a hydrogenated polybutadiene skeleton, urethane (meth)acrylate having a polycarbonate skeleton, urethane (meth)acrylate having a hydrogenated bisphenol A skeleton, urethane (meth)acrylate having a polyether skeleton, urethane (meth)acrylate having a polyester skeleton, and urethane (meth)acrylate having a castor oil skeleton.

[0045] Examples of the epoxy (meth)acrylate include epoxy (meth)acrylates obtained by reacting a conventionally known epoxy resin, such as an aromatic epoxy resin, an alicyclic epoxy resin, or an aliphatic epoxy resin, with (meth)acrylic acid.

[0046] The molecular weight of the polymer and / or oligomer having two or more (meth)acryloyl groups in one molecule is preferably a weight average molecular weight of 15,000 or less, more preferably 14,000 or less, and even more preferably 13,000 or less. The lower limit of the weight average molecular weight is, for example, 500.

[0047] The glass transition temperature (Tg) of the polymer and / or oligomer having two or more (meth)acryloyl groups in one molecule is preferably 50° C. or less, more preferably 25° C. or less, even more preferably 5° C. or less, and particularly preferably 0° C. or less. The lower limit is, for example, −50° C.

[0048] The Tg of the polymer and oligomer was calculated from the maximum value of tan δ in the measurement of the storage modulus. Specifically, a photoinitiator was added to the polymer or oligomer, and a cured product of 5 mm x 50 mm x 1 mm was prepared by irradiating it with ultraviolet light (UV). The storage modulus (E'), loss modulus (E''), and loss tangent (tan δ = E'' / E') were measured using a dynamic viscoelasticity device (DMA6100) under conditions of a frequency of 1 Hz, a heating rate of 2°C / min, and a temperature range of -60°C to 200°C, and the maximum value of tan δ was obtained and taken as the Tg.

[0049] The difunctional ethylenically unsaturated compound monomer is not particularly limited, and examples thereof include 1,3-butylene glycol di(meth)acrylate, 1,4-butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexane glycol di(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, ethylene oxide modified neopentyl glycol di(meth)acrylate, and propylene oxide. Examples of the polyether ether derivatives include modified neopentyl glycol di(meth)acrylate, hydroxypivalic acid ester neopentyl glycol diacrylate, caprolactone-modified hydroxypivalic acid ester neopentyl glycol diacrylate, neopentyl glycol-modified trimethylolpropane di(meth)acrylate, stearic acid-modified pentaerythritol di(meth)acrylate, dicyclopentenyl di(meth)acrylate, ethylene oxide-modified dicyclopentenyl di(meth)acrylate, di(meth)acryloyl isocyanurate, and dimethyloltricyclodecane di(meth)acrylate.

[0050] The anaerobically curable adhesive composition according to the present disclosure may contain one type of bifunctional ethylenically unsaturated compound alone, or may contain two or more types of bifunctional ethylenically unsaturated compounds. From the viewpoints of anaerobic curability and peel strength, the content of the bifunctional ethylenically unsaturated compound is preferably 20 mass% to 60 mass%, more preferably 25 mass% to 55 mass%, and even more preferably 30 mass% to 50 mass%, relative to the total mass of the anaerobic curing adhesive composition.

[0051] <Anaerobic curing catalyst> The anaerobic curing adhesive composition according to the present disclosure preferably contains an anaerobic curing catalyst. Examples of anaerobic curing catalysts include saccharin, amine compounds, azole compounds, mercaptan compounds, hydrazine compounds, and salts thereof. Among these, a combination of saccharin and a hydrazine compound or a salt thereof is preferred from the viewpoint of anaerobic curing properties.

[0052] Saccharin may have some hydrogen atoms substituted, and for example, N-methylsaccharin can be preferably used in addition to saccharin.

[0053] Examples of the amine compound include heterocyclic secondary amines such as 1,2,3,4-tetrahydroquinoline and 1,2,3,4-tetrahydroquinaldine, etc.; heterocyclic tertiary amines such as quinoline, methylquinoline, quinaldine and quinoxalinephenazine, etc.; and aromatic tertiary amines such as N,N-dimethyl-anisidine, N,N-dimethylaniline and N,N'-dimethyl-p-toluidine.

[0054] Examples of the azole compound include 1,2,4-triazole, oxazole, oxadiazole, thiadiazole, benzotriazole, hydroxybenzotriazole, benzoxazole, 1,2,3-benzothiadiazole, and 3-mercaptobenzotriazole.

[0055] Examples of the mercaptan compound include linear mercaptans such as n-dodecyl mercaptan, ethyl mercaptan, and butyl mercaptan.

[0056] Examples of the hydrazine compound include 1-acetyl-2-phenylhydrazine, 1-acetyl-2(p-tolyl)hydrazine, 1-benzoyl-2-phenylhydrazine, 1-(1',1',1'-trifluoro)acetyl-2-phenylhydrazine, 1,5-diphenyl-carbohydrazine, 1-formyl-2-phenylhydrazine, 1-acetyl-2-(p-bromophenyl)hydrazine, 1-acetyl-2-(p-nitrophenyl)hydrazine, 1-acetyl-2-(2'-phenylethylhydrazine), p-nitrophenylhydrazine, and p-trisulfonylhydrazide. Examples of salts of hydrazine compounds include 4-methylsulfonylphenylhydrazine hydrochloride, hydrazine monohydrochloride, and p-tolylhydrazine hydrochloride.

[0057] The anaerobic curing adhesive composition according to the present disclosure may contain one type of anaerobic curing catalyst alone, or may contain two or more types of anaerobic curing catalysts. From the viewpoints of anaerobic curing property and peel strength, the content of the anaerobic curing catalyst is preferably 0.01 mass % to 5 mass %, more preferably 0.03 mass % to 3 mass %, and even more preferably 0.05 mass % to 1 mass %, relative to the total mass of the anaerobic curing adhesive composition.

[0058] <Radical polymerization initiator> The anaerobic curing adhesive composition according to the present disclosure preferably contains a radical polymerization initiator. Examples of the radical polymerization initiator include a thermal radical polymerization initiator and a photoradical polymerization initiator. From the viewpoint of anaerobic curability, the thermal radical polymerization initiator is preferred.

[0059] The thermal radical polymerization initiator is not particularly limited, but examples thereof include organic peroxides and azo compounds, and among these, organic peroxides are particularly preferred.

[0060] Examples of the organic peroxide include hydroperoxides such as cumene hydroperoxide, t-butyl hydroperoxide, p-methane hydroperoxide, methyl ethyl ketone peroxide, cyclohexane peroxide, dicumyl peroxide, and diisopropylbenzene hydroperoxide, as well as other organic peroxides such as ketone peroxides, diallyl peroxides, and peroxy esters. Examples of the azo compound include azobisisobutyronitrile, azobisisovaleronitrile, and azobisisocapronitrile. Among these, hydroperoxides are preferably used from the viewpoint of storage stability.

[0061] From the viewpoint of excellent anaerobic curing properties, the organic peroxide is preferably an organic peroxide having a one-hour half-life temperature in the range of 80° C. to 300° C., and more preferably an organic peroxide having a one-hour half-life temperature in the range of 100° C. to 200° C. The one-hour half-life temperature is a value measured by pyrolysis in benzene at a peroxide concentration of 0.1 mol / L.

[0062] Examples of organic peroxides having a one-hour half-life temperature in the range of 80° C. to 300° C. include hydroperoxides. Specific examples of hydroperoxides include p-menthane hydroperoxide, diisopropylbenzene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, cumene hydroperoxide, and t-butyl hydroperoxide.

[0063] The photoradical polymerization initiator is not particularly limited, but examples thereof include acetophenone-based photoradical polymerization initiators, benzoin-based photoradical polymerization initiators, benzophenone-based photoradical polymerization initiators, thioxanthone-based photoradical polymerization initiators, acylphosphine oxide-based photoradical polymerization initiators, and titanocene-based photoradical polymerization initiators.

[0064] Examples of acetophenone-based photoradical polymerization initiators include diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, benzyl dimethyl ketal, 4-(2-hydroxyethoxy)phenyl(2-hydroxy-2-propyl)ketone, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-2-morpholino(4-thiomethylphenyl)propan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, and 2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propanone oligomer. Commercially available acetophenone-based photoradical polymerization initiators include Omnirad 184, Omnirad 1173, Omnirad 2959, Omnirad 127 (manufactured by IGM Resins BV), and ESACURE KIP-150 (manufactured by Lamberti spa). Examples of the acylphosphine oxide-based photoradical polymerization initiator include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, etc. Commercially available acylphosphine oxide-based photoradical polymerization initiators include Omnirad TPO, Omnirad 819 (manufactured by IGM Resins BV), and Omnirad 819DW (manufactured by IGM Resins BV).

[0065] The anaerobically curable adhesive composition according to the present disclosure may contain one type of radical polymerization initiator alone, or may contain two or more types. The content of the radical polymerization initiator is preferably in the range of 10 mass % or less, relative to the total mass of the anaerobic curing adhesive composition, and from the viewpoint of anaerobic curability, is more preferably 0.01 mass % to 10 mass %, even more preferably 0.05 mass % to 8 mass %, and particularly preferably 0.1 mass % to 5 mass %, relative to the total mass of the anaerobic curing adhesive composition.

[0066] <Polymerization inhibitor> The anaerobic curing adhesive composition according to the present disclosure also preferably contains a polymerization inhibitor. Examples of the polymerization inhibitor include organic polymerization inhibitors, inorganic polymerization inhibitors, and organic salt polymerization inhibitors.

[0067] Specific examples of organic polymerization inhibitors include phenolic compounds such as hydroquinone, tert-butylhydroquinone, hydroquinone monomethyl ether, p-methoxyphenol, 2,6-di-tert-butyl-4-methylphenol, 2,4,6-tri-tert-butylphenol, and 4-tert-butylcatechol; quinone compounds such as benzoquinone; oxalic acid, phenothiazine; and N-nitroso-N-phenylhydroxylamine ammonium. Examples of inorganic polymerization inhibitors include copper chloride, copper sulfate, and iron sulfate. Examples of the organic salt polymerization inhibitor include copper dibutyldithiocarbamate, disodium ethylenediaminetetraacetic acid, and aluminum N-nitroso-N-phenylhydroxylamine.

[0068] The anaerobic curing adhesive composition according to the present disclosure may contain one type of polymerization inhibitor alone, or may contain two or more types of polymerization inhibitors. From the viewpoint of storage stability, the content of the polymerization inhibitor is preferably 0.001 mass % to 2 mass %, more preferably 0.002 mass % to 1 mass %, and particularly preferably 0.005 mass % to 0.1 mass %, relative to the total mass of the anaerobic curing adhesive composition.

[0069] <Adhesion promoter> The anaerobic curing adhesive composition according to the present disclosure also preferably contains an adhesion promoter. Unlike the anaerobic curing catalyst, the adhesion promoter does not directly cure the anaerobic adhesive, but is a component that improves the adhesive strength of the anaerobic adhesive. The adhesion promoter is preferably soluble in the diluent. The adhesion promoter is preferably one that contains a functional group or element that can chemically or physically interact with the metal contained in the adherend, and an adhesion promoter containing such a functional group or element can have a high effect of improving the adhesive strength of the anaerobic curing adhesive composition. In order to impart adhesion, the adhesion promoter is preferably a compound that partially corrodes the metal surface by chemical action, or a compound that forms a covalent bond or hydrogen bond with the hydroxyl group present on the adherend surface. Examples of the functional group include -OH, -COOH, and -SH. The elements include phosphorus and nitrogen. Furthermore, the adhesion promoter may have a radical polymerizable group (a group having an ethylenically unsaturated bond). When the adhesion promoter has a radical polymerizable group, the adhesive strength of the adhesive to the adherend can be further improved. In this specification, the above-mentioned alicyclic (meth)acrylates, (meth)acrylate phosphates, silane coupling agents, and bifunctional ethylenically unsaturated compounds are treated as being different from adhesion promoters for the sake of convenience.

[0070] Examples of the adhesion promoter include compounds containing nitrogen atoms, organic acids, and organic acid derivatives. Examples of compounds containing nitrogen atoms include radical polymerizable monomers and aromatic amines containing nitrogen atoms, and specific examples thereof include phenylmaleimide and acryloylmorpholine. Examples of organic acids and organic acid derivatives include compounds containing multiple acid functional groups in one molecule (phthalic acid, trimellitic acid, pyromellitic acid, etc.), organic acids having radical polymerizable groups ((meth)acrylic acid, etc.), and acid anhydrides of the organic acids.

[0071] The anaerobic curing adhesive composition according to the present disclosure may contain one type of adhesion promoter alone, or may contain two or more types of adhesion promoter, and may contain an acid and an acid anhydride in combination. From the viewpoints of anaerobic curability and peel strength, the content of the adhesion promoter is preferably 0.01 to 10 mass %, and more preferably 0.05 to 5 mass %, relative to the total mass of the anaerobic curing adhesive composition.

[0072] <Other ingredients> The anaerobic curing adhesive composition according to the present disclosure may contain additives such as fillers, crosslinking agents, various elastomers, storage stabilizers, antioxidants, light stabilizers, heavy metal deactivators, tackifiers, plasticizers, defoamers, pigments, rust inhibitors, leveling agents, dispersants, rheology adjusters, and flame retardants, provided such additives do not impair the object of the present disclosure.

[0073] The anaerobically curable adhesive composition according to the present disclosure may contain a filler to the extent that it does not impair storage stability, for the purpose of improving the storage modulus, flowability, etc. of the cured product. Specific examples of such a filler include organic powders and inorganic powders.

[0074] Examples of inorganic powder fillers include, but are not limited to, glass, fumed silica, alumina, mica, ceramics, silicone rubber powder, calcium carbonate, aluminum nitride, carbon powder, kaolin clay, dried clay minerals, and dried diatomaceous earth. The content of the inorganic powder is preferably 0.1 to 100 parts by mass per 100 parts by mass of the polymerization components (the total content of the ethylenically unsaturated compounds (bifunctional ethylenically unsaturated compounds, (meth)acrylates, phosphate (meth)acrylates, etc.) and the silane coupling agent, the same applies below).

[0075] Fumed silica is blended for the purpose of adjusting the viscosity of the anaerobic curing adhesive composition or improving the mechanical strength of the cured product. Preferably, fumed silica surface-treated with dimethylsilane, trimethylsilane, alkylsilane, methacryloxysilane, organochlorosilane, polydimethylsiloxane, hexamethyldisilazane, or the like is used. Commercially available fumed silica products include, for example, Aerosil® R972, R972V, R972CF, R974, R976, R976S, R9200, RX50, and NA. X50, NX90, RX200, RX300, R812, R812S, R8200, RY50, NY50, RY200S, RY200, RY300, R104, R106, R202, R805, R816, T805, R711, RM50, R7200, etc. (all manufactured by Nippon Aerosil Co., Ltd.).

[0076] The organic powder filler is not particularly limited, but examples thereof include polyethylene, polypropylene, nylon (registered trademark), cross-linked acrylic, cross-linked polystyrene, polyester, polyvinyl alcohol, polyvinyl butyral, polycarbonate, and the like. The content of the organic powder is preferably 0.1 to 100 parts by mass with respect to 100 parts by mass of the polymerizable components.

[0077] The anaerobic curing adhesive composition according to the present disclosure may contain an antioxidant. Examples of the antioxidant include quinone compounds such as β-naphthoquinone, 2-methoxy-1,4-naphthoquinone, methylhydroquinone, hydroquinone, hydroquinone monomethyl ether, mono-tert-butylhydroquinone, 2,5-di-tert-butylhydroquinone, p-benzoquinone, 2,5-diphenyl-p-benzoquinone, and 2,5-di-tert-butyl-p-benzoquinone; phenothiazine, 2,2-methylene-bis(4-methyl-6-tert-butylphenol), catechol, tert-butylcatechol, and 2-butyl-4 -Hydroxyanisole, 2,6-di-tert-butyl-p-cresol, 2-tert-butyl-6-(3-tert-butyl-2-hydroxy-5-methylbenzyl)-4-methylphenyl acrylate, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, 4,4'-butylidenebis(6-tert-butyl-3-methylphenol), 4,4'-thiobis(6-tert-butyl-3-methylphenol), 3,9-bis[2-[3-(3-tert-butyl ethyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5,5]undecane, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], thiodiethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, N,N'-hexane-1,6-diylbis[3-(3,5-di -tert-butyl-4-hydroxyphenyl)propionamide], benzenepropanoic acid, 3,5-bis(1,1-dimethylethyl)-4-hydroxy-, C7-C9 side chain alkyl ester, 2,4-dimethyl-6-(1-methylpentadecyl)phenol, diethyl [[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]phosphonate, 3,3',3”,5,5',5”-hexa-tert-butyl-a,a',a”-(mesitylene-2,4,6-tolyl)tri-p-cresol, calcium diethylbis[[3,5- Bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]phosphonate, 4,6-bis(octylthiomethyl)-o-cresol, ethylene bis(oxyethylene)bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate], hexamethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trimethyl-2,4,6(1H,3H,5H)-triphenylphosphine phenols such as 1,3,5-tris[(4-tert-butyl-3-hydroxy-2,6-xylyl)methyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, reaction products of N-phenylbenzenamine with 2,4,6-trimethylpentene, 2,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazin-2-ylamino)phenol, picric acid, and citric acid; tris(2,4-di-tert-butylphenyl)phosphite, tris[2-[[2, 4,8,10-Tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphen-6-yl]oxy]ethyl]amine, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis[2,4-bis(1,1-dimethylethyl)-6-methylphenyl]ethyl ester phosphorous acid, tetrakis(2,4-di-tert-butylphenyl)[1,1-bisphenyl]-4,4'-diyl bisphosphonite, 6-[3-(3-tert-butyl-4-hydroxy-5-methyl Examples of suitable compounds include phosphorus compounds such as 2,4,8,10-tetra-tert-butyldibenz[d,f][1,3,2]dioxaphosphene; sulfur compounds such as dilauryl 3,3'-thiodipropionate, dimyristyl 3,3'-thiodipropionate, distearyl 3,3'-thiodipropionate, pentaerythrityl tetrakis(3-laurylthiopropionate), 2-mercaptobenzimidazole; amine compounds such as phenothiazine; lactone compounds; and vitamin E compounds. Among these, phenol compounds are preferred.

[0078] The method for producing the anaerobic curing adhesive composition according to the present disclosure is not particularly limited, and the composition can be produced by a known method. For example, the composition can be produced by mixing predetermined amounts of each component with a mixing means such as a mixer at a temperature of preferably 10°C to 100°C for preferably 0.1 to 5 hours.

[0079] From the viewpoint of the ease of spreading of the anaerobic curing adhesive composition applied to a metal material, the viscosity of the anaerobic curing adhesive composition according to the present disclosure at 25°C is preferably 10,000 mPa·s or less, more preferably 5,000 mPa·s or less, and even more preferably 3,000 mPa·s or less. The lower limit of the viscosity is, for example, 10 mPa·s or more. The viscosity of the anaerobic curing adhesive composition according to the present disclosure is a value measured in accordance with JIS Z 8803:2011. Specifically, a specified amount of the anaerobic curing adhesive composition is taken and dispensed into a measuring cup. The viscosity is measured at 25°C using a TVE22H (manufactured by Toki Sangyo Co., Ltd.).

[0080] [Cured product] The cured product according to the present disclosure is obtained by curing the above-mentioned anaerobic curing adhesive composition. The shape of the cured product according to the present disclosure is not particularly limited, but is preferably a cured film.

[0081] The method for curing the anaerobic curing adhesive composition according to the present disclosure may be, for example, curing at room temperature (20° C. to 30° C.), or heating may be performed as necessary.

[0082] The storage modulus at 25°C of the cured product of the anaerobic curing adhesive composition according to the present disclosure is 10 9 Pa or less, and 8 The lower limit of the storage modulus at 25° C. is preferably 10 Pa or less. 5 Pa or more, 10 6The storage modulus at 100° C. of the cured product of the anaerobic curing adhesive composition according to the present disclosure may be 10 Pa or more from the viewpoint of strength expression at high temperatures. 8 Pa or less, and 7 The lower limit of the storage modulus at 100° C. is preferably 10 Pa or less. 4 It can be 10 Pa or more. 5 The storage modulus may be in the above range, which results in superior peel strength and operability.

[0083] From the viewpoint of adhesion of the resulting cured product to a substrate, the glass transition temperature (Tg) of the anaerobic curing adhesive composition according to the present disclosure is preferably 150° C. or lower, and more preferably 120° C. or lower. The lower limit of the glass transition temperature (Tg) of the cured product is 70° C. or higher.

[0084] The storage modulus is a value measured in accordance with JIS K 7244. Specifically, using a dynamic viscoelasticity measuring device (product name "MCR301" manufactured by Anton Paar), the anaerobic curing adhesive composition is applied to a jig for the dynamic viscoelasticity measuring device coated with AT QUICKA CM manufactured by Toagosei, and the storage modulus is measured under the conditions of a frequency of 1 Hz, a temperature of 25°C, and a thickness of 0.3 mm. The product in which it has been confirmed that there is no change in the storage modulus is regarded as a cured product. Using the above cured product, the storage modulus (G'), loss modulus (G"), and loss tangent (tan δ=G" / G') due to shear are measured in the range of -30°C to 150°C at a frequency of 1 Hz and a heating rate of 2°C / min. In the present disclosure, "there is no change in the storage modulus" means that the rate of change in the storage modulus per minute is 1% or less of the final storage modulus at 25°C.

[0085] [Laminate] The laminate of the present disclosure includes a first substrate, a second substrate, and an adhesive layer that bonds the first substrate and the second substrate. The adhesive layer is formed using a cured product of the anaerobic curing adhesive composition.

[0086] In the present disclosure, the material of the first substrate and the second substrate is not particularly limited, and examples thereof include plastic, wood, metal, inorganic material, and paper. Examples of plastics include polyvinyl alcohol, cellulose acetate resins such as triacetyl cellulose and diacetyl cellulose, acrylic resins, polyethylene terephthalate, polycarbonate, polyarylate, polyethersulfone, cyclic polyolefin resins having cyclic olefins as monomers such as norbornene, polyvinyl chloride, epoxy resins, and polyurethane resins. Wood includes, for example, natural wood and synthetic wood. Examples of metals include metals such as steel plate, aluminum, stainless steel, and chromium, and metal oxides such as zinc oxide (ZnO) and indium tin oxide (ITO). Inorganic materials include, for example, glass, mortar, concrete, and stone. Among these, metals are particularly preferred from the viewpoint of peeling resistance under high-temperature water conditions.

[0087] The shape of the first substrate and the second substrate is not particularly limited, but may be flat or may have a three-dimensional structure. Examples of the three-dimensional structure include screw members (e.g., screws and screw holes, etc.), fitting members (e.g., protruding members and recessed members, and rod members and hole members, etc.). Among them, it is suitable for use in flat substrates.

[0088] The thickness of the adhesive layer is not particularly limited, and from the viewpoints of the curability of the anaerobic curing adhesive composition and the peel strength under high-temperature water conditions, it is preferably 0.5 μm to 50 μm, more preferably 0.5 μm to 30 μm, even more preferably 0.8 μm to 25 μm, and particularly preferably 1.0 μm to 20 μm.

[0089] The method for producing the laminate according to the present disclosure is not particularly limited and can be appropriately selected depending on the purpose, etc. For example, a method including a step of applying a primer composition containing a solvent and an organometallic complex to at least one of a first substrate and a second substrate (e.g., a metal material), a step of applying an anaerobic curing adhesive composition to at least one of a first substrate and a second substrate (e.g., a metal material), and a step of bonding the other substrate (e.g., a second substrate (e.g., a metal material)) to one substrate (e.g., a first substrate (e.g., a metal material)) to which the anaerobic curing adhesive composition has been applied can be preferably exemplified.

[0090] The primer composition used in the present disclosure is not particularly limited, and examples thereof include compositions obtained by diluting an organometallic complex (copper ethylhexanoate, iron pentadione, cobalt pentadione, copper pentadione, propylenediamine copper, ethylenediamine copper, iron naphthate, nickel naphthate, cobalt naphthate, copper naphthate, copper octate, iron hexoate, iron propionate, vanadium acetylacetonate, etc.) with a solvent (ethanol, toluene, acetone, heptone, etc.).

[0091] The method for applying the primer composition and the anaerobic curing adhesive composition is not particularly limited, and any known method can be used. Examples of the application means include roller, dispensing, spray, inkjet, dipping, etc.

[0092] In the above-described preferred method, heating can be performed after the step of laminating the other substrate (e.g., a second substrate (e.g., a metal material)). Heating can cure the anaerobic curing adhesive composition in a shorter time. The heating method is not particularly limited, and examples thereof include a method using a thermostatic bath, a far-infrared heater, and the like. The heating temperature and time may be any conditions that allow curing, and are preferably 40°C to 300°C (more preferably 60°C to 150°C) and 10 seconds to 3 hours (more preferably 20 seconds to 60 minutes). When a thermostatic bath is used, it is preferable to fix the laminate with a fixing jig or the like before placing it in the thermostatic bath, which can prevent positional deviation.

[0093] When the adhesive layer in the laminate is peeled off from the first substrate or the second substrate, the average peel strength under high-temperature water conditions at 95° C. is preferably 0.3 N / mm or more, more preferably 0.4 N / mm or more, and even more preferably 0.5 N / mm or more. The upper limit of the average peel strength under high-temperature water conditions at 95° C. is, for example, 10 N / mm or less.

[0094] In the present disclosure, the average peel strength under a high-temperature water condition of 95° C. is a value measured as follows. A water bath is used to heat the water bath to 90°C to 100°C (center temperature 95°C), and then the laminate is immersed in the warm water of the water bath, and one minute after immersion, T-peel is performed in the water bath at a speed of 10 mm / min. T-peel is performed by bending parts of the two stainless steel plates that make up the laminate by 90° each, and pulling them in a direction at an angle of 90° to the in-plane direction of the laminate as shown in Figure 1. The average peel strength of the parts where the measurement results were stable is calculated and used as the average peel strength. EXAMPLES

[0095] Hereinafter, the present disclosure will be described in more detail with reference to examples, but the present disclosure is not limited to the following examples as long as it does not deviate from the gist of the disclosure. In addition, unless otherwise specified, "parts" are based on mass.

[0096] (Examples 1 to 7, Comparative Examples 1 to 10) <Preparation of Anaerobic Curing Adhesive Composition> The components shown in Table 1 below were mixed in a mixer for 60 minutes at room temperature (25° C.) so as to have the contents shown in Table 1, thereby obtaining anaerobic curing adhesive compositions of Examples 1 to 7 and Comparative Examples 1 to 10.

[0097] Details of each component listed in Table 1 below are explained below.

[0098] <Difunctional ethylenically unsaturated compounds> Genomer 4256: Aliphatic urethane methacrylate (molecular weight 10,580, Tg=-10℃, functional group number=2, RAHN)

[0099] <Alicyclic methacrylate> CHMA: Cyclohexyl methacrylate (Tg=66℃, Kyoeisha Chemical Co., Ltd., product name: "Light Ester CH") IBXMA: Isobornyl methacrylate (Tg=180℃, Kyoeisha Chemical Co., Ltd.: Product name "Light Ester IB-X")

[0100] <Straight-chain methacrylate> HEMA: 2-hydroxyethyl methacrylate (Tg=55℃, Mitsubishi Gas Chemical Co., Ltd.)

[0101] <Methacrylate phosphate> · Hosmer M: 2-Methacryloyloxyethyl acid phosphate (Unichemical Co., Ltd.) · Hosmer CL: ({1-chloro-3-[(2-methylprop-2-enoyl)oxy]propan-2-yl}oxy)phosphonic acid (Methacrylate phosphate with halogen atoms in the side chain, Unichemical Co., Ltd.) Light Ester P-1M: 2-Methacryloyloxyethyl acid phosphate (Kyoeisha Chemical Co., Ltd.) Light Ester P-2M: Di-(2-methacryloyloxyethyl) phosphate (Kyoeisha Chemical Co., Ltd.)

[0102] <Silane coupling agent> ·KBM-503: 3-Methacryloxypropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd.) ·KBM-803: 3-Mercaptopropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd.)

[0103] <Anaerobic curing catalyst> ·N,N-Dimethyl-p-toluidine (FUJIFILM Wako Pure Chemical Industries, Ltd.) N-Methylsaccharin (Tokyo Chemical Industry Co., Ltd.)

[0104] <Polymerization inhibitor> Q-1301: N-nitroso-N-phenylhydroxylamine aluminum (FUJIFILM Wako Pure Chemical Industries, Ltd.)

[0105] <Radical polymerization initiator> CHP: Cumene hydroperoxide (NOF Corp.: product name "Percumyl H")

[0106] <Adhesion promoter> HOA-MPL: 2-acryloyloxyethyl-phthalate (Kyoeisha Chemical Co., Ltd.: product name "HOA-MPL") 4-Methylphthalic anhydride (Tokyo Chemical Industry Co., Ltd.) Acrylic acid (Toagosei Co., Ltd.)

[0107] <Primer> ·AT Quicker CM (manufactured by Toagosei Co., Ltd.)

[0108] <Preparation of Laminate> Two stainless steel plates (SUS304, Engineering Test Service Co., Ltd.) were used as substrates. The substrates were degreased with acetone. The above primer was applied to one side of one substrate, and the prepared anaerobic curing adhesive composition was applied to one side of the other substrate. Next, two stainless steel plates were bonded together by bringing the surface of one substrate coated with the primer into contact with the surface of the other substrate coated with the anaerobic curing adhesive composition, and the plates were pressed together with a spacer using a press (high pressure jack "J-15K", AS ONE Corporation) so that the thickness of the adhesive layer of the anaerobic curing adhesive composition was 20 μm. After pressing, the plates were left to stand overnight at 25° C. to obtain a laminate.

[0109] [viscosity] The viscosity (mPa·s) of the anaerobic curing adhesive composition was measured in accordance with JIS Z 8803:2011 using a TVE22 viscometer (manufactured by Toki Sangyo Co., Ltd.) at a temperature of 25° C. under the following conditions. (Examples 1, 2, 7, Comparative Examples 5, 6, 10): A cone plate of 1°34' x R24 was used, and the rotation speed was 5 rpm. (Examples 3 to 6, Comparative Examples 7 to 9): A cone plate of 1°34' x R24 was used, and the rotation speed was 10 rpm.

[0110] [Storage modulus and glass transition temperature] The storage modulus of the cured product of the anaerobic curing adhesive composition was measured in accordance with JIS K 7244. The glass transition temperature (Tg) was calculated from the maximum tan δ value (tan δmax) in the measurement of the storage modulus. In Table 1, "-" in the columns for storage modulus and glass transition temperature indicates that the measurement was not performed. Specifically, a dynamic viscoelasticity measuring device (product name "MCR301" manufactured by Anton Paar) was used to apply the anaerobic curing adhesive composition to a jig for the dynamic viscoelasticity measuring device coated with AT QUICKA CM manufactured by Toagosei, and then the storage modulus was measured under the conditions of a frequency of 1 Hz, a temperature of 25°C, and a thickness of 0.3 mm. The product in which it was confirmed that there was no change in the storage modulus was defined as a cured product. The above cured product was used to measure the storage modulus (G'), loss modulus (G"), and loss tangent (tan δ=G" / G') due to shear in the range of -30°C to 150°C at a frequency of 1 Hz and a heating rate of 2°C / min. In the present disclosure, "there is no change in the storage modulus" means that the rate of change in the storage modulus per minute is 1% or less of the final storage modulus at 25°C.

[0111] [Average peel strength] A water bath was used to adjust the temperature of the water bath to 90°C to 100°C (center temperature 95°C), and then the laminate prepared above was immersed in the warm water of the water bath, and one minute after immersion, T-shaped peeling was performed in the water bath at a speed of 10 mm / min. The T-shaped peeling was performed by bending parts of the two stainless steel plates that make up the laminate by 90° each, and pulling them in a direction at an angle of 90° to the in-plane direction of the laminate as shown in Figure 1. The average peel strength of the parts where the measurement results were stable was calculated and used as the average peel strength.

[0112] [Table 1]

[0113] As shown in Table 1, the anaerobic curing adhesive compositions of Examples 1 to 7 were shown to have superior peel strength under high-temperature water conditions compared to the anaerobic curing adhesive compositions of Comparative Examples 1 to 10.

Claims

1. Contains at least an alicyclic (meth)acrylate and a (meth)acrylate phosphate (excluding those containing a halogen atom in the side chain), The anaerobic curing adhesive composition has a total content of the (meth)acrylate phosphate and the silane coupling agent of 1 mass % or more and 10 mass % or less, based on the total amount of the anaerobic curing adhesive composition, and the content of the silane coupling agent is less than 5 mass % based on the total amount of the anaerobic curing adhesive composition.

2. The anaerobically curable adhesive composition according to claim 1 , which comprises a difunctional ethylenically unsaturated compound.

3. 3. The anaerobic curing adhesive composition according to claim 1, wherein the content of the alicyclic (meth)acrylate is from 30% to 70% by mass, based on the total amount of the anaerobic curing adhesive composition.

4. The anaerobically curable adhesive composition according to claim 2 , wherein the content of the bifunctional ethylenically unsaturated compound is from 20% by mass to 60% by mass, based on the total amount of the anaerobically curable adhesive composition.

5. 3. The anaerobically curable adhesive composition according to claim 2, wherein the bifunctional ethylenically unsaturated compound is a polymer or oligomer having two or more (meth)acryloyl groups in one molecule.

6. 6. The anaerobic curing adhesive composition according to claim 5, wherein the polymer or oligomer having two or more (meth)acryloyl groups in one molecule has a weight average molecular weight of 15,000 or less and a glass transition temperature of 0°C or less.

7. The anaerobically curable adhesive composition according to claim 1 or 2, wherein the silane coupling agent has a thiol group.

8. 3. The anaerobic curing adhesive composition according to claim 1, having a viscosity at 25° C. of 50 mPa·s to 1,000 mPa·s.

9. A cured product obtained by curing the anaerobic curing adhesive composition according to claim 1 or 2.

10. A laminate comprising a first substrate, an adhesive layer, and a second substrate in this order, the adhesive layer comprising the cured product according to claim 9.

11. The laminate according to claim 10, wherein the average peel strength under a high-temperature water condition of 95°C when peeling the adhesive layer from the first substrate or the second substrate is 0.3 N / mm or more.

Citation Information

Patent Citations

  • Anaerobically curable adhesive

    JP2016117851A

  • Radical-polymerizable adhesive composition for adhesive laminated steel sheet, adhesive laminate, motor and method for producing adhesive laminate

    WO2019123885A1

Cited By

  • Steel sheet laminate production method, steel sheet laminate, and adhesive composition

    WO2025197894A1